Striatal Dopamine Transporter and Rest Tremor in Parkinson Disease - Niemi, Kalle J.; Jaakkola, Elina; Myller, Elina Maaria; Eklund, Mikael R. E.; Nuuttila, Simo; Mertsalmi, Tuomas; Murtomäki, Kirsi-Marja; Levo, Reeta; Noponen, Tommi; Ihalainen, Toni; Scheperjans, Filip; Joutsa, Juho; et al. (Advanstar Communications, 2026)
Background and Objectives
The mechanisms underlying tremor generation in Parkinson disease (PD) remain unclear. Previously, we demonstrated a connection between rest tremor amplitude and higher dopamine transporter (DAT) binding in the ipsilateral striatum among the Parkinson Progression Markers Initiative cohort. Here, we investigated the association of parkinsonian motor symptoms with striatal DAT binding in a sizable and clinically representative sample of patients with parkinsonian signs to validate the previously observed ipsilateral relationship in PD.
Methods
This observational cross-sectional study included right-handed patients referred for [123I]FP-CIT SPECT because of clinically uncertain parkinsonism or tremor at Turku University Hospital and the Helsinki and Uusimaa Hospital District, Finland. Each patient underwent a comprehensive clinical evaluation and follow-up (median 3.0 years [interquartile range (IQR) 2.5]). Associations between striatal tracer binding and symptoms were investigated using voxel-wise linear models, adjusting for age, sex, motor symptom severity, and medication. The primary outcome measure was the association between rest tremor amplitude and striatal DAT binding.
Results
At the end of the follow-up period, of the 414 patients included (median age 68 years [IQR 14], 49.4% female), 148 were evaluated to have PD and 79 other forms of parkinsonism with striatal DAT deficit. In total, 187 patients had normal binding. Among the patients with PD, left and right rest tremor amplitudes were positively associated with ipsilateral striatal DAT binding (β = +0.12 [95% CI +0.05, +0.19] and +0.10 [+0.05, +0.15] specific binding ratio [SBR] per point; pFWE + Bonf. < 0.05, respectively). Left and right bradykinesia (β = −0.16 [−0.22, −0.09] and −0.18 [−0.25, −0.10] SBR per 5 points, pFWE + Bonf. < 0.05, respectively) and rigidity (β = −0.07 [−0.08, −0.04] and −0.08 [−0.11, −0.05] SBR per point, pFWE + Bonf. < 0.05, respectively) mainly showed a negative association with contralateral striatal DAT binding. No consistent associations were observed in non-PD groups.
Discussion
These findings confirm the positive association between rest tremor amplitude and ipsilateral striatal DAT binding in a clinical sample of PD patients. However, the non-PD groups were diagnostically heterogeneous, limiting conclusions about disease specificity.